1997
DOI: 10.1007/s004380050364
|View full text |Cite
|
Sign up to set email alerts
|

MADS box genes expressed in developing inflorescences of rice and sorghum

Abstract: With the aim of elucidating the complex genetic system controlling flower morphogenesis in cereals, we have characterized two rice and two sorghum MADS box genes isolated from cDNA libraries made from developing inflorescences. The rice clones OsMADS24 and OsMADS45, which share high homology with the Arabidopsis AGL2 and AGL4 MADS box genes, are expressed in the floral meristem, in all the primordia, and in mature floral organs. High expression levels have also been found in developing kernels. The sorghum clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 33 publications
(38 reference statements)
1
39
0
3
Order By: Relevance
“…The WSEP homoeologs belong to the Os MADS45-type cluster, and the WLHS1 homoeologs belong to the Os MADS1-type cluster. In the Os MADS45-type cluster, there are two rice genes, Os MADS24 and Os MADS45 (Greco et al, 1997). WSEP genes formed a subcluster with Os MADS45 that was distinct from Os MADS24.…”
Section: Identification Of Class E Mads Box Genes In Wheatmentioning
confidence: 99%
“…The WSEP homoeologs belong to the Os MADS45-type cluster, and the WLHS1 homoeologs belong to the Os MADS1-type cluster. In the Os MADS45-type cluster, there are two rice genes, Os MADS24 and Os MADS45 (Greco et al, 1997). WSEP genes formed a subcluster with Os MADS45 that was distinct from Os MADS24.…”
Section: Identification Of Class E Mads Box Genes In Wheatmentioning
confidence: 99%
“…OsMADS45 shares homology with Arabidopsis SEP1 (AGL2) and SEP2 (AGL4) (Pelaz et al, 2000) and was shown to be expressed in floral organs in whorl 2, 3 and 4 of wild-type flowers (Greco et al, 1997) (Fig. 7C).…”
Section: Interaction Between Spw1 and DLmentioning
confidence: 99%
“…OsMADS1 (Chung et al, 1994), ZMM3, ZMM6 , OsMADS24, SbMADS1 (Greco et al, 1997), TM5 (Pnueli et al, 1991), FBP2 (Angenent et al, 1994), AGL2 (Ma et al, 1991) and ZMM2 b After Fischer et al (1995). Fig.…”
unclassified
“…In monocots, MADS box genes have been cloned from orchid (Lu et al, 1993), maize (Schmidt et al, 1993), rice (Chung et al, 1994), and sorghum (Greco et al, 1997). However, little is known about the functions of MADS box genes in monocots, although the MADS box genes are believed to play substantial roles on floral organ identity.…”
mentioning
confidence: 99%